Faktor-Faktor yang Berhubungan dengan Kejadian Kecelakaan Kerja di Laboratorium Pendidikan - Dwi Cahyaningrum; Hanif Tegar Muktiana Sari; Dini Iswandari (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Laboratory occupational safety is an action to prevent the occurrence of accident in laboratory environment caused by design, system, process and activities in laboratory. Laboratory with all desain and activities have a potencial hazard of accident. This study aimed to know factors related with the incident of accident in education laboratory. This is a cross sectional study with quantitative approach. Primary data was collected using questionnaire to 30 student in the last semester. Data were analyzed using chi square test at significance level at 0,05.  The result show that the most accident occurred in laboratory are contact with the hot object, exposed to chemical spills, and also asphyxiation.  The results  also show that there is no related between the application of standart operated procedure and the knowledge level of student with the incident of occupational accident, and there is a relation between the use of personal protective equipment with the incident of occupational accident in education laboratory